Bibliometrik Analysis: Kontruksi Sosial Masyarakat Mengenai Teknologi AI Pada Data Base Scoupus 2014-2024 - Nisa Dienwati Nuris; Khaerul Anam; Dadang Sudrajat (Prosiding SISFOTEK, 2024)
This research investigates the social construction of ChatGPT technology in society by identifying and analyzing the factors that influence its adoption and utilization. Through this analysis, we aim to identify recent research trends, gaps, and future research opportunities. The study utilizes data from various international scientific journals indexed by Scopus to explore the application of social construction of technology techniques and their societal impact. The method used in this research is bibliometric analysis to uncover patterns in the study of the social construction of ChatGPT technology in society. The results show that user perceptions of ChatGPT are influenced by digital readiness, technological literacy, as well as perceptions of benefits and risks. Additionally, ChatGPT is closely related to the development of critical skills among students, supporting the enhancement of analytical and critical abilities. The research focus in the field of AI, particularly concerning social and economic impacts, is expanding. This study emphasizes the importance of AI in various aspects of life and its contribution to sustainable development, especially in higher education, where AI technology integration is involved. Educational institutions are encouraged to design policies to support learning and skill development through AI. This research has limitations, particularly in terms of sample size and methodology, which can be addressed in future studies by expanding the scope and methods of the research. Overall, this study enriches the understanding of the impact of AI technology, particularly ChatGPT, in higher education and provides a foundation for further research.